Blood Biochemical Components and Progesterone Hormone on Day of Estrus in Crossbred Cattle in Egypt - R. S. Mourad (Jurnal Ilmu Ternak dan Veteriner, 2018)
Deficiencies or excess minerals such as P, Cu, and Zn are associated with subnormal fertility and anoestrus conditions in cows. This study was conducted in a veterinary unit in Menufiya, Egypt.  Eighteen head of crossbred cows were randomly selected at random at estrus time (estrus group) and as a control 14 head of crossbred cows were selected from newly-calving dams at about 6-12 hours after calving (control group). The aim of this study was to use the components of biochemistry and progesterone hormone on estrus day of crossbreeding cattle in Egypt.  The information from this study will be used to confirm estrus time to improve mating percentage. In blood plasma, the concentrations of all biochemical components and progesterone concentrations in estrus animals are higher than control cows except globulin. The results showed that blood plasma from control animal obtained Mg, Ca / P ratio, Co, Cu, Zn, Se, and Mo concentration is higher than estrus cattle. On the other hand, blood plasma concentrations of Na, K, Ca, P, Mn, and Fe are higher in estrus cattle. The progesterone concentration of estrus cattle is lower during summer than in winter. In estrus cows, higher plasma macro-elements were found in winter than in summer except for K, Ca and Ca/P ratio.  On the other side of estrus cattle, all trace elements of blood plasma are higher in winter than in summer except Zn, Mn, Se, and Fe.